2019
DOI: 10.1002/ar.24110
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hypoxia in Corneal Extracellular Matrix Deposition and Cell Motility

Abstract: The cornea is an excellent model tissue to study how cells adapt to periods of hypoxia as it is naturally exposed to diurnal fluxes in oxygen. It is avascular, transparent, and highly innervated. In certain pathologies, such as diabetes, limbal stem cell deficiency, or trauma, the cornea may be exposed to hypoxia for variable lengths of time. Due to its avascularity, the cornea requires atmospheric oxygen, and a reduction in oxygen availability can impair its physiology and function. We hypothesize that hypoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…Hypoxia is a well-known inducer of angiogenesis [28,29,51,52,53]. Indeed, several previous studies have also found a link between hypoxia and ECM remodeling [54,55,56]. Hypoxia-induced alterations include changes in composition and mechanical properties, namely ECM stiffness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxia is a well-known inducer of angiogenesis [28,29,51,52,53]. Indeed, several previous studies have also found a link between hypoxia and ECM remodeling [54,55,56]. Hypoxia-induced alterations include changes in composition and mechanical properties, namely ECM stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted the present studies on tissue culture plastic, which is a non-physiologically stiff substrate, especially compared to the retina, thus, it would be interesting to explore if hypoxia also modulates the stiffness of the RPE ECM by culturing cells on softer gels. Indeed, a recent study of corneal epithelial cells noted significant differences in the response of these cells to hypoxia based on the stiffness of the matrix used [55]. This is interesting in light of our previous work showing that VEGF responsiveness of endothelial cells is modulated by matrix stiffness [57,58] and that the ability of heparin and heparan sulfate to regulate Fn structure, and VEGF binding site availability, is responsive to mechanical force applied to the Fn fibers [59].…”
Section: Discussionmentioning
confidence: 99%
“…The result of mechanical forces can be seen in endothelial vasculature [1], bone remodeling [2], and cell-cell communication between vascular endothelial cells on substrata [3]. In addition, when epithelial cells migrate they generally move as a sheet of cells to heal a wound rather than discrete cells and we hypothesize that the sheet generates unique forces on the underlying basement membrane depending on the stiffness of the substrate [4]. The motility of the sheet is enabled by protrusion of lamellipodia at the leading edge of the wound and requires a continual assembly and disassembly of focal adhesions that occur during extension, retraction, maturation of nascent adhesions [5].…”
Section: Introductionmentioning
confidence: 98%
“…More recently Onochie et al, demonstrated that the leading-edge dynamics of migrating corneal epithelium were significantly different on a substrate of 8kPa compared to a stiffer substrate. In addition, there was a significantly greater phosphorylation of focal adhesion kinase proteins when cells were cultured and wounded on stiffer substrata [4].…”
Section: Introductionmentioning
confidence: 99%
“…This article compares normal and hypoxia environments on corneal epithelia in two systems, a 3D corneal organ culture and substrates of varying stiffness. They show that low‐oxygen environments alter the composition of the ECM, basal lamina stiffness, and focal adhesion dynamics (Onochie et al, 2020). The next three articles explore unique cell–cell communication mechanisms.…”
mentioning
confidence: 99%